2007
DOI: 10.1007/s00253-007-1105-7
|View full text |Cite
|
Sign up to set email alerts
|

The three tricarboxylate synthase activities of Corynebacterium glutamicum and increase of l-lysine synthesis

Abstract: Corynebacterium glutamicum owns a citrate synthase and two methylcitrate synthases. Characterization of the isolated enzymes showed that the two methylcitrate synthases have comparable catalytic efficiency, k (cat)/K (m), as the citrate synthase with acetyl-CoA as substrate, although these enzymes are only synthesized during growth on propionate-containing media. Thus, the methylcitrate synthases have a relaxed substrate specifity, as also demonstrated by their activity with butyryl-CoA, whereas the citrate sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Given that PrpR was the name given to the 54 -dependent regulator of the prp operon of enterobacteria (18,19), Masiewicz et al (27) used the same nomenclature for Rv1129c, despite its dissimilarity in amino acid sequence to PrpR. This name was also later used for describing Cg0800 of C. glutamicum (29,55). Because PrpR/LrpG (Rv1129c) from M. tuberculosis and PrpR (Cg0800) from C. glutamicum are members of the MccR class of the ScfR family, we recommend adjusting the previously mixed and misleading nomenclature (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given that PrpR was the name given to the 54 -dependent regulator of the prp operon of enterobacteria (18,19), Masiewicz et al (27) used the same nomenclature for Rv1129c, despite its dissimilarity in amino acid sequence to PrpR. This name was also later used for describing Cg0800 of C. glutamicum (29,55). Because PrpR/LrpG (Rv1129c) from M. tuberculosis and PrpR (Cg0800) from C. glutamicum are members of the MccR class of the ScfR family, we recommend adjusting the previously mixed and misleading nomenclature (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of cellular oxaloacetate concentrations seems to be crucial, especially for improving L-lysine production. This possibility was proposed by Menkel et al (29) and was indicated by overexpression of the pyruvate carboxylase gene (40), inactivation of PEP carboxykinase (46), inactivation of citrate and methylcitrate synthases (45), and disruption of the malate:quinone oxidoreductase gene (31). However, there have not been many studies addressing the role of oxaloacetate decarboxylase (ODx), an enzyme that has high levels of activity in different C. glutamicum strains (21) and catalyzes the irreversible decarboxylation of oxaloacetate (25), at this key branch point.…”
mentioning
confidence: 99%
“…Later, two methylcitrate synthases were identified, PrpC1 (cg0798) and PrpC2 (cg0762), which also can catalyze the formation of citrate from oxaloacetate and acetylCoA (47). Their activity usually is not sufficient to substitute for the one of GltA, but enhanced prp gene expression due to the inactivation of the repressor PrpR allows for the partial complementation of a ⌬gltA mutant (47).…”
mentioning
confidence: 99%
“…The relevance of individual TCA cycle enzymes in C. glutamicum has been explored with the help of mutants in which the corresponding genes were disrupted or deleted, such as strains lacking citrate synthase (13,47), isocitrate dehydrogenase (12), 2-oxoglutarate dehydrogenase (25), malate-quinone oxidoreductase (41), and malate dehydrogenase (40,41). In the case of citrate synthase, which catalyzes the first, irreversible step of the TCA cycle, this approach revealed the presence of alternative enzymes which can at least partially take over the function of the deleted protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation